Aktivitas Antibakteri In-Vitro Ekstrak Etanol Beberapa Jenis Tanaman Krokot (Portulaca sp) - Agus Purwanto AP (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
Purslane has antibacterial benefits. The diversity of purslane plants from the genus Portulaca is about 40-100 species found in tropical and four-season areas. The aim of this study was to test the in-vitro antibacterial potential of the ethanol extract of some purslane (Portulaca sp) cultivars against the tested bacteria. In-vitro antibacterial activity testing was performed using the disc diffusion method. This study used Portulaca oleracea and Portulaca grandiflora purslane cultivars. The results of the observation of the antibacterial activity testing of several cultivars of Portulaca grandiflora (K1, K3) and Portulaca oleracea (K2) against the test bacteria Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa were able to show antibacterial activity with various inhibition zones ranging between 1.56 cm and 2.86 cm. Based on the results of testing for antibacterial activity of several cultivars of purslane plant, it was shown that the sensitivity of the Gram-positive test bacteria Staphylococcus aureus was higher than the Gram-negative test bacteria Escherichia coli and Pseudomonas aeruginosa.Â Keywordsâ€”: Portulaca oleracea, Portulaca grandiflora, disc diffusion method